Degenerative spine disease: Italian position paper on acquisition, interpretation and reporting of Magnetic Resonance Imaging - Pizzini, Francesca B.; Poletti, Mattia; Beltramello, Alberto; Muto, Mario; Splendiani, Alessandra; Mehrabi, Sara; Costanzo, Giuseppe; Vitiello, Vincenzo; Barile, Antonio; Colagrande, Stefano; Mansueto, Giancarlo; Bastianello, Stefano (Insights into imaging, 2021)
Objective To promote a better radiological interpretation of spine degeneration, a consistent standardization of the acquisition, interpretation and description of Magnetic Resonance Imaging (MRI) l findings. Materials and methods In order to achieve this objective, a consensus among experts in imaging of degenerative spine disease (DSD) from Italian radiological societies (SIRM—Italian Society of Radiology, AINR—Italian Association of Neuroradiology) was achieved. The representatives of the Italian inter-societal working group examined the literature produced by European/American task forces on optimizing the study sequences, classification of degenerative disc changes, spondylo-arthrosis, osteochondrosis, synovial and ligament pathologies of the spinal column, and on canal and foraminal stenosis. The document-resulted from the consensus between experts—was then presented to the scientific societies of Neurosurgery (SINCH) and Orthopedics and Traumatology (SIOT) for their approval. Results This position paper presents a proposal for an optimized MRI protocol for studying DSD and provides a glossary of terms related to this pathology and indications on their use. The international terminological recommendations have been translated and adapted to the Italian language and clinical practice and clinical cases have been used to illustrate some of the main classifications. Conclusions This revision of international DSD guidelines/recommendations and consensus made it possible to (1) update the nomenclature to international standards and (2) harmonize the MRI protocol and description of radiological findings, adapting both (1, 2) to the Italian context. With this position paper we intend to contribute to an improvement of the communication among doctors and between physicians and their patients as well as the quality of the radiological reports.